Stability of singular waves for Dullin–Gottwald–Holm equation. (April 2022) - Gao, Yuetian; Chen, Jianze
Abstract: In this paper, the asymptotic stability of the solutions near the explicit singular waves of Dullin–Gottwald–Holm equation is studied based on the commutator estimate, the semi-group theory of linear operator and the Banach fixed point theorem.